Eribulin as first-line treatment in older patients with advanced breast cancer: A multicenter phase II trial [SAKK 25/14]. Issue 1 (January 2023) - Hasler-Strub, Ursula; Mueller, Andreas; Li, Qiyu; Thuerlimann, Beat; Ribi, Karin; Gerber, Stefan; von Moos, Roger; Fehr, Mathias; Rochlitz, Christoph; Zaman, Khalil; Aebi, Stefan; Hochstrasser, Andreas; et al.
Abstract: Introduction: Standard-dose eribulin mesylate (1.4 mg/m 2 d1 + 8) achieves clinical benefit rates of 26%–52% in patients with metastatic breast cancer (mBC). <10% of patients in the registration trial were ≥ 70 years old; dose reductions were common in these older patients. Materials and Methods: This single-arm phase II trial explored the efficacy of reduced starting dosing of first-line eribulin at 1 mg/m 2 d1 + 8 q3 weeks in patients with mBC aged ≥70 years. The primary endpoint was a disease control rate (DCR) ≥55%. The secondary endpoints were objective response (OR), progression-free survival (PFS), overall survival (OS), and patient-reported neurotoxicity. Results: Overall, 77 patients were accrued; their median age was 76 years and Eastern Cooperative Oncology Group performance status was 0–1 in 90%. The DCR was 40% (90% confidence interval [CI]: 31–50); therefore, the primary endpoint was not reached. The overall response rate was 22% (95%CI: 13–33), median PFS 5.4 months (95%CI: 4.5–7.7), and median OS 16.1 months (95%CI: 13.5–26.9). Dose modifications were necessary in 35% of patients. In nine patients, more than fifteen cycles were given; 48 patients (62%) experienced at least one grade 3 toxicity. Median patient-reported neurotoxicity scores remained stable for at least fifteen cycles. The main reason for treatment discontinuation was disease progression (57%). Discussion: We report the first prospective data on first-line eribulin in older patients. The reduced starting dose of 1.1 mg/m 2 was safe, with prolonged treatment and DC achieved in a considerable proportion of patients (but less than the 55% assumed), without cumulative neurotoxicity. The reduced dose was apparently within the range of the minimal effective dose, as shown by the efficacy lack in patients requiring further dose reductions. Thus, our results do not support the approach of a reduced starting dose for older patients.